Fasting blood glucose, blood pressure and body mass index among combined oral contraceptive users in Chencha town Southern Ethiopia, 2019 - Kofole, Zelalem; Haile, Diresbachew; Solomon, Yerukneh (Frontiers in Global Women's Health, 2023)
Background The use of contraceptives has become prevalent among women in Ethiopia. Oral contraceptive use has been suggested to trigger changes in glucose metabolism, energy expenditure, blood pressure, and body weight, among various populations and ethnic groups. Objective To elucidate the pattern of fasting blood glucose, blood pressure, and body mass index among combined oral contraceptive pills users compared to controls. Methods An institution-based cross-sectional study design was employed. A total of 110 healthy women using combined oral contraceptive pills were recruited as cases. Another 110 healthy age and sex-matched women not using any hormonal contraceptives were recruited as controls. A study was conducted between October 2018 and January 2019. Data obtained was entered and analyzed using IBM SPSS version 23 software packages. One-way ANOVA was used to identify the variation of variables in relation to the duration of use of the drug. The P-value of < 0.05 at the 95% confidence level was statistically significant. Results Fasting blood glucose level among oral contraceptive users (88.55 ± 7.89 mg/dl) was higher than fasting blood glucose level among oral contraceptive non-users (86.00 ± 9.85 mg/dl) with a p-value of 0.025. The mean arterial pressure of oral contraceptive users (88.2 ± 8.48 mmHg) was relatively higher than their counterparts (86.0 ± 6.74 mmHg), with a p-value of 0.04. Comparatively the body weight and body mass index among oral contraceptive users were 2.5% and 3.9% higher than non-users with a p-value of 0.03 and 0.003, respectively(5). Utilization of oral contraceptive pills for prolonged period of time seemed to be a significant predictive factor for higher mean arterial pressure and body mass index with p < 0.001and p < 0.05 respectively. Conclusions Use of combined oral contraceptives was associated with higher fasting blood glucose (+2.9%), mean arterial pressure (+2.5%), and body mass index (3.9%) compared to controls.